La experiencia de una infraestructura financiera semi-formal en países en vías de desarrollo: propuestas para el Brasil y América Latina - Castro Carvalho, André (2013)
The government usually seeks help from private investors to be able to deliver public services. Private capital usually tends to concentrate on big profi table projects. In order to be able to carry out the smaller projects, an alternative to privatizations has to be proposed, in attention to the State’s inefficiency to deliver every service the society demands. In this article, the author proposes the civil society’s active participation as a way to carry out smaller projects efficiently. Nonetheless, civil participation is not possible without an attractive foment policy and the facilitation of particular initiatives given by the State. The article focuses particularly in the case of the Brazilian reality and other parts of LatinAmerica.